2001
DOI: 10.1002/dvdy.10051
|View full text |Cite
|
Sign up to set email alerts
|

Green fluorescent protein expression in germ‐line transmitted transgenic zebrafish under a stratified epithelial promoter from Keratin8

Abstract: A zebrafish cDNA encoding a novel keratin protein was characterized and named keratin8, or krt8. krt8 expression was initiated at 4.5 hr postfertilization, immediately after the time of zygotic genome activation. The expression is limited to a single layer of envelope cells on the surface of embryos and, in later stages, it also appears in the innermost epithelial layer of the anterior-and posteriormost portions of the digestive tract. In adult, its expression was limited to the surface layer of stratified epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
106
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(111 citation statements)
references
References 38 publications
(57 reference statements)
3
106
0
2
Order By: Relevance
“…The Ds element harbored the EGFP gene regulated by the zebrafish 2.25-kb keratin 8 (krt8) promoter (Gong et al 2002) between the 59-and 39-end cisrequired sequences (Weil and Kunze 2000) ( Figure 1A). The second construct harboring the coding sequence of the truncated Ac transposase (TPase 103-807 ) (Houba-Herin et al 1990), fused to a synthetic nuclear localization signal analogous to that of the SV40 large T antigen, was also generated ( Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ds element harbored the EGFP gene regulated by the zebrafish 2.25-kb keratin 8 (krt8) promoter (Gong et al 2002) between the 59-and 39-end cisrequired sequences (Weil and Kunze 2000) ( Figure 1A). The second construct harboring the coding sequence of the truncated Ac transposase (TPase 103-807 ) (Houba-Herin et al 1990), fused to a synthetic nuclear localization signal analogous to that of the SV40 large T antigen, was also generated ( Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
“…To produce the NLS-TPase-EGFP and NLS K5E -TPase-EGFP fusion constructs, we amplified NLS-TPase and NLS K5E -TPase fragments by PCR using primers AGAGGGATCCAGCTCA GAATAAACGCTCAAC and AGAGACCGGTCCTGGAGAGG AGCCACTTGCTA and cloned the fragments in AgeI and BamHI sites of the krt8-EGFP plasmid (Gong et al 2002). To produce NLS-EGFP and NLS K5E -EGFP constructs, we deleted the Ac TPase 103-807 open reading frame (ORF) sequence from the NLS-TPase-EGFP and NLS K5E -TPase-EGFP constructs using the QuikChange site-directed mutagenesis kit (Stratagene) and primers AGAAGAAGCGTAAGGTAGAAATGGTG AGCAAGGGCGAGGAGC and GCTCCTCGCCCTTGCTCAC CATTTCTACCTTACGCTTCTTCT.…”
Section: Methodsmentioning
confidence: 99%
“…Basal epithelial cell labeling was also performed by injection of DNA constructs containing a fluorescent protein under the control of a basal cell-specific Np63 promoter (Reischauer et al, 2009). Suprabasal labeling was achieved by expression via a keratin promoter (Gong et al, 2002). Several pulses of a micropoint laser (435 nm) were used to produce wounds on both sides of the epithelial fold.…”
Section: Morphodynamic Profiling Of Epithelial Sheet Motion By Particmentioning
confidence: 99%
“…GFP-UtrCH was PCR amplified from pCS2+GFP-UtrCH and ClaIBamH1 cloned into pME. To construct plasmids for transient mosaic expression or the generation of stable transgenic zebrafish, the tol2kit system was used (Kwan et al, 2007); pME-AKT-PH-GFP, pME-AKT-PH-mKate2, or pME-GFP-UtrCH were combined with plasmids containing either the actb2 (Higashijima et al, 1997) or keratin4 (krt4; previously krt8; Gong et al, 2002) promoters and an SV40 poly-A sequence into the pDestTol2CG2 backbone (Kwan et al, 2007) using gateway cloning (Invitrogen). N-p63: Gal4,UAS:GFP was generated as described previously (Reischauer et al, 2009).…”
Section: Velocimetry Analysismentioning
confidence: 99%
“…Cell types of the teleost developing skin may be unambiguously identified with molecular markers or after they display their characteristic mature forms. For example, keratins may be used as marker for keratinocyte differentiation but some of them are also expressed in the EVL (Imboden et al, 1997;Chua and Lim, 2000;Gong et al, 2002;Wang et al, 2006). In situ hybridization experiments have also revealed that embryonic epidermal cells are able to start the expression type I collagen ␣2 chain (col1a2) transcript between 24 and 48 hpf to at least 26 dpf (Le Guellec et al, 2004).…”
Section: Epidermis Molecular Patterning and The Role Of Rbp4 Apoeb mentioning
confidence: 99%